Exploring Self-Efficacy in Women’s Leadership: A Case Study of the Subdistrict Head of Tegal Barat, Tegal City, Central Java - Fikri, Alfin; Sugiharto, Unggul; Widodo, Agus Setio (TEMALI : Jurnal Pembangunan Sosial, 2025)
This study aims to analyze the self-efficacy of Teti Kirnawati, SKM, MH, the female subdistrict head in Tegal Barat, and its impact on leadership performance in public administration. This research explores how self-efficacy influences a woman’s ability to succeed in leadership roles within a male-dominated public sector. Using a qualitative approach, this study employs techniques such as interviews, observations, and document analysis. The findings show that Teti Kirnawati’s self-efficacy, shaped by her professional experience, social support, and strong self-belief, plays a crucial role in her success in leading and making confident decisions. The study also reveals how family support, education, and role models contribute to strengthening women’s self-efficacy in public office. The implications of this research highlight the need to strengthen gender equality by empowering women through education, social support, and the removal of structural barriers. The study suggests that women with high self-efficacy can play a significant role in improving the quality of governance. This research contributes new insights to the study of female leadership in Indonesia and offers practical insights for policies aimed at creating a more inclusive environment for women in government.